The New Indices of Religious Orientation Revised (NIROR): A Study among Canadian Adolescents Attending a Baptist Youth Mission and Service Event - Francis, Leslie J. (Religions, 2016)
This study explores the properties of the New Indices of Religious Orientation Revised (NIROR) among a sample of 521 Canadian adolescents attending a Baptist youth mission and service event, ranging in age from 12 to 19 years. This revision simplified the language of the original instrument to increase its accessibility among young people. The data support the internal consistency reliability and construct validity of the three revised nine-item scales designed to operationalise extrinsic religious orientation, intrinsic religious orientation, and quest religious orientation.